Involvement of Serotonergic System in Oxaliplatin-Induced Neuropathic Pain - Ji Hwan Lee; Woojin Kim (Biomedicines, 2021)
Oxaliplatin is a chemotherapeutic agent widely used against colorectal and breast cancers; however, it can also induce peripheral neuropathy that can rapidly occur even after a single infusion in up to 80–90% of treated patients. Numerous efforts have been made to understand the underlying mechanism and find an effective therapeutic agent that could diminish pain without damaging its anti-tumor effect. However, its mechanism is not yet clearly understood. The serotonergic system, as part of the descending pain inhibitory system, has been reported to be involved in different types of pain. The malfunction of serotonin (5-hydroxytryptamine; 5-HT) or its receptors has been associated with the development and maintenance of pain. However, its role in oxaliplatin-induced neuropathy has not been clearly elucidated. In this review, 16 in vivo studies focused on the role of the serotonergic system in oxaliplatin-induced neuropathic pain were analyzed. Five studies analyzed the involvement of 5-HT, while fourteen studies observed the role of its receptors in oxaliplatin-induced allodynia. The results show that 5-HT is not involved in the development of oxaliplatin-induced allodynia, but increasing the activity of the 5-HT1A, 5-HT2A, and 5-HT3 receptors and decreasing the action of 5-HT2C and 5-HT6 receptors may help inhibit pain.